EFEKTIFITAS PEMBERIAN BHD TERHADAP KEBERHASILAN HENTI NAPAS - Nurfadilla, Nurfadilla; Tanra, Andi Husni; Wahab, Iswan (Universitas Pahlawan, 2024)
The aim of this study is to explore the effectiveness of basic life support (BLS) in improving the success of respiratory arrest management. Through a literature review, this study highlights the importance of a quick and precise response in the implementation of BLS, as well as the role of extensive community training and collaboration between authorities and the medical community. The research method used is a qualitative method, involving in-depth analysis of various sources related to BLS and best practices in respiratory arrest situations. Data were collected from journal articles, books, and relevant health institution reports, and then analyzed to identify key factors influencing BLS effectiveness. The conclusion of this study indicates that the success of BLS heavily depends on individual skills and knowledge, the support of medical facilities such as automated external defibrillators in public places, and strong collaboration between health authorities and the medical community. With joint efforts to enhance training and the availability of medical facilities, the survival chances of individuals experiencing respiratory arrest can be significantly increased.